Pesticides Updates on Toxicity, Efficacy and Risk Assessment - Larramendy, Marcelo L.; Soloneski, Sonia (IntechOpen, 2022)
Pesticides - Updates on Toxicity, Efficacy and Risk Assessment examines different aspects of pesticides encountered in both anthropogenic and natural environments, and provides valuable information on the toxicity, efficacy and risk assessment of several compounds that can have a negative effect on the health of living species and ecosystems. We hope that the real-life examples from diverse sources provided in this book will extend the appreciation of the complexity of this subject in a way that may stimulate new approaches in relevant fields.